Use of next‐generation sequencing and candidate gene analysis to identify underlying defects in patients with inherited platelet function disorders. (27th January 2015) - Leo, V. C.; Morgan, N. V.; Bem, D.; Jones, M. L.; Lowe, G. C.; Lordkipanidzé, M.; Drake, S.; Simpson, M. A.; Gissen, P.; Mumford, A.; Watson, S. P.; Daly, M. E.; et al.
Summary Background Inherited platelet function disorders (PFDs) are heterogeneous, and identification of the underlying genetic defects is difficult when based solely on phenotypic and clinical features of the patient. Objective To analyze 329 genes regulating platelet function, number, and size in order to identify candidate gene defects in patients with PFDs. Patients/methods Targeted analysis of candidate PFD genes was undertaken after next‐generation sequencing of exomic DNA from 18 unrelated index cases with PFDs who were recruited into the UK Genotyping and Phenotyping of Platelets (GAPP) study and diagnosed with platelet abnormalities affecting either Gi signaling (n = 12) or secretion (n = 6). The potential pathogenicity of candidate gene defects was assessed using computational predictive algorithms. Results Analysis of the 329 candidate PFD genes identified 63 candidate defects, affecting 40 genes, among index cases with Gi signaling abnormalities, while 53 defects, within 49 genes, were identified among patients with secretion abnormalities. Homozygous gene defects were more commonly associated with secretion abnormalities. Functional annotation analysis identified distinct gene clusters in the two patient subgroups. Thirteen genes with significant annotation enrichment for 'intracellular signaling' harbored 16 of the candidate gene defects identified in nine index cases with Gi signaling abnormalities. Four gene clusters, representing 14 genes, with significantly associated gene ontology annotations were identified among the cases with secretion abnormalities, the most significant association being with 'establishment of protein localization.' Conclusion Our findings demonstrate the genetic complexity of PFDs and highlight plausible candidate genes for targeted analysis in patients with platelet secretion and Gi signaling abnormalities.